ANALISA PENJADWALAN DAN PENGENDALIAN BIAYA PROYEK TANGGUH EXPANSION PROJECT, BINTUNI PAPUA BARAT - Rizky Tri Astuti; sely novita sari; anggi hermawan (Retii, 2022)
ABSTRACT Projects generally have a deadline, which means they must be completed before or exactly at the appointed time. Tangguh Expansion Project is a mega project that builds an LNG refinery well located in Bintuni Bay, West Papua, to accommodate natural gas. Phase III of the project began to be built in 2017 with a completion target of 2019. However, the project had delays due to several things, such as the difficult terrain, limited manpower, and limited materials. There is a time limit on construction activities the project planning must be calculated appropriately. Overcoming the delay, so requires an analysis of the acceleration of implementation time so that the project can be completed according to schedule and planned costs. The data processing process applied in this study uses scheduling and financing with the Critical Path Method (CPM) and is carried out with programs called Microsoft Excel and Microsoft Project. The results of the acceleration of the duration of the Tangguh Expansion Project, Bintuni West Papua using This CPM method projects 162 days faster than the planned duration. So that the optimal duration is obtained project of 558 days from the planned duration of 720 days with time efficiency optimization results of 22.5% which can save costs of Rp. 1.150.060.443,74 and the cost efficiency is 8,8%. Keywords: Duration, Cost, CPM, Acceleration